The Use of ISO 27001 Framework for Government’s Online E-Monitoring System Implementation - Pini Singgrit; Geraldi Catur Pamuji (Peneliti.net, 2020)
This research aims to discover the security level of online e-monitoring information system in Karawang Regency Government. We used Information Security Management System (ISMS), ISO 27001 11th paragraph access control Annex A 11.2, and Annex A 11.3 as the orientation of information security governance. It also used to actualize good government’s information security system. This research method was done using Plan-Do-Check-Act (PDCA) questionnaire. The questionnaire was addressed to two kinds of respondents: users and leaders. The results of this study is that (1) users’ trust the security level is 52% dan (2) leaders trust the security level is 48%. According to the results, ISMS on the online e-monitoring system in Karawang Regency Government is unsafe because it is under 64% based on ISO 27001 Standardization. In this research, we propose an ISMS framework designed to manage the secrecy aspect, integrity, and information security. This framework was developed based on ISO 27001 Standardization. By applying this ISMS framework in Karawang Regency Government, this research is expected to reduce the information security threat in data center and support organization in the future.